The Effect of Convenience, Trust, and Security on Purchasing Decisions Through Tokopedia (A Case Study of Tokopedia Users in Cirebon City) - Chrisdino, Billy; Yusuf, Yusuf (Journal Research of Social Science, Economics, and Management, 2026)
The rapid development of technology in e-commerce in Indonesia has intensified competition among platforms, highlighting the importance of understanding the factors that influence consumers’ purchasing decisions. This study aims to analyze how convenience, trust, and security affect the purchasing decisions of Tokopedia users, particularly in Cirebon City. The research employed a quantitative approach with an associative method. Data were collected using a questionnaire distributed via Google Forms to 170 respondents who had made at least one purchase on Tokopedia within the past six months. A purposive sampling technique was used in this study. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the SmartPLS application. The results indicate that convenience, trust, and security have a positive and significant effect on purchasing decisions, both partially and simultaneously, with an R² value of 0.646, indicating that 64.6% of the variance in purchasing decisions can be explained by these three variables. It can therefore be concluded that convenience, trust, and security have a positive and significant influence on the purchasing decisions of Tokopedia users in Cirebon City, both partially and simultaneously.